Yttrium-90 radioembolization for hepatocellular carcinoma: Outcome prediction with MRI derived fat-free muscle area. Issue 125 (April 2020) - Faron, Anton; Sprinkart, Alois M.; Pieper, Claus C.; Kuetting, Daniel L.R.; Fimmers, Rolf; Block, Wolfgang; Meyer, Carsten; Thomas, Daniel; Attenberger, Ulrike; Luetkens, Julian A.
Highlights: Fat-free muscle area (FFMA) predicts survival in advanced hepatocellular carcinoma. FFMA as a measure of sarcopenia can be opportunistically derived from routine diagnostic MRI. FFMA may represent a promising new imaging biomarker for survival prognosis in radioembolization. Abstract: Purpose: Sarcopenia is associated with adverse outcomes in several gastrointestinal malignancies and liver cirrhosis. We aimed to study the utility of magnetic resonance imaging (MRI) derived fat-free muscle area (FFMA) to predict clinical outcome in patients receiving yttrium-90 radioembolization (RE) for treatment of hepatocellular carcinoma (HCC). Methods: Fifty-eight patients with unresectable HCC and pre-interventional liver MRI undergoing salvage RE were retrospectively evaluated. Using axial T2-weighted turbo spin echo sequences, FFMA was calculated by subtraction of the intramuscular adipose tissue area from the total cross-sectional area of paraspinal skeletal muscles at the superior mesenteric artery level. FFMA values lower than 3582 mm 2 in male and 2301 mm 2 in female patients were defined as low FFMA. Main outcomes were progression-free survival (PFS) and overall survival (OS). For outcome analysis, the Kaplan-Meier method with log rank test and multivariate cox regression analysis were used. Results: Mean time from pre-interventional MRI to RE was 27 ± 20 days. Median OS and PFS after RE were 250 (range: 21–1230 days) and 156 days (range: 21–674 days), respectively. Patients with low FFMA showed significantly reduced OS (197 vs. 294 days, P = 0.024) and tended to have shortened PFS (109 vs. 185 days, P = 0.068). Low FFMA (HR 2.675; P = 0.011), estimated liver tumor burden (HR 4.058; P = 0.001), and Eastern Cooperative Oncology Group (ECOG) performance status (1.763; P = 0.009) were independent predictors of OS on multivariate analysis. Conclusions: FFMA as a measure of sarcopenia predicts OS and might represent a promising new biomarker for survival prognosis in patients undergoing RE for treatment of unresectable HCC.